The detection and phylogenetic characterization of Cryptosporidium, Cystoisospora, and Giardia duodenalis of cats in South Korea - Chi Sun Yun; Bo-Youn Moon; Kichan Lee; Su Min Kang; Bok-Kyung Ku; Mi-Hye Hwang (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionCryptosporidium, Cystoisospora, and Giardia duodenalis are gastrointestinal protozoa parasites that cause diarrhea in various animals. However, information regarding the detection and phylogenetic characterization of gastrointestinal protozoa parasites in cats is limited throughout South Korea. Therefore, this study aimed to determine the detection and identify subspecies of gastrointestinal protozoa parasites in cats from South Korea. MethodsA total of 290 fecal samples were collected from stray, companion, and shelter cats in six provinces. Cryptosporidium, Cystoisospora, and G. duodenalis were identified by PCR. All positive samples were subtyped by PCR and sequencing of gp60, ITS-1, tpi, bg, and gdh. ResultsThe overall detection of gastrointestinal protozoan parasitic infection was 17.93%. G. duodenalis was the most prevalent, with 7.93%, followed by Cystoisospora spp. (7.24%) and Cryptosporidium spp. (4.48%). In addition, C. felis (n=10), C. parvum (n=2), C. ryanae (n=1), Cystoisospora felis (n=14), Cystoisospora suis (n=5), Cystoisospora ohioensis (n=1), Cystoisospora spp. were identified in subspecies analysis of positive samples. C. felis showed a significant association with diarrhea (7.81%) and living condition (6.04%), and Cystoisospora felis in diarreha (9.38%) according to detection. Through phylogenetic analysis of the tpi, bg, and gdh genes from 23 G. duodenalispositive samples, it was confirmed that the samples of present study belonged to assemblage A, B, C, and D. DiscussionSouth Korean cats have a high rate of gastrointestinal protozoan parasites infection with cat-specific Cryptosporidium and Cystoisospora, which are associated with living conditions and diarrhea symptoms. Moreover, zoonotic and other animal-specific subtype of protozoan parasites have been detected in cat feces.